Mechanical Properties of Full Size Kapur (Dryobalanops Spp.) Beams and Correlation for Different NDT Methods - Duju, Alik (2002)
To cope with a large number of species and difficulties in species identification of tropical timbers, development of strength grading would be highly needed for an efficient and effective utilisation of structural components of our tropical timbers. To do that, an acceptable method of predicting timber strength has to be established in order to develop the confidence in using timbers as construction materials. A total of 6 species of Kapur (Dryobalanops spp.) namely, Kapur bukit (Dryobalanops beccarii Dyer), Kapur empedu (Dryoba/anops Fusca V. SI.), Kapur kelansau (Dryobalanops oblongifolia Dyer), Kapur paji (Oryobalanops lanceolata Burck), Kapur paya (Dryobalanops rappa Becc.) and Kapur peringgi (Dryobalanops sumatrensis (J. F. Gmelin) Kosterm) were used in this study. The trees selected for sampling possessed a healthy grown, straight bole and with minimum diameter of 450 mm were collected from Mixed Dipterocarp Forest and Peat Swamp Forest. The sampling of test specimens was made throughout the whole lengths of tree bole.